Studi Kualitatif Implementasi Kebijakan Eliminasi Malaria di Wilayah Endemis Rendah Kabupaten Pangandaran dan Pandeglang - Tri Wahono; Endang Puji Astuti; Andri Ruliansyah; Mara Ipa; Muhammad Umar Riandi (ASPIRATOR - Journal of Vector-borne Disease Studies, 2021)
The government targets malaria elimination in Java and Bali by 2023. But until 2020, Pangandaran and Pandeglang Regency haven’t received malaria-free certification. This qualitative study was conducted to provide an overview of Pangandaran and Pandeglang malaria control implementation by comparing it to Activity Indicators based on the Indonesian Minister of Health Decree on malaria elimination. In-depth interviews, using thematically interview guidelines, were conducted to 48 key informants such as policyholders and people in charge of health programs and cross-sectoral at the provincial, district, sub-district, and village levels. Thematic analysis was used in the theme of policy implementation, budget, facilities and infrastructures, human resources, and cross-sector cooperation. The result shows that malaria control is implemented according to the decree, but some activities haven’t been done. The analysis on policy implementation theme shows that both districts have carried out according to the guidelines, with innovation in the form of establishing Posmaldes (village malaria post) in Ujung Kulon National Park in Pandeglang. APBD, APBN, and Global Fund are used as budget sources. Both districts stated that facilities and infrastructures are sufficiently available, but there is a lack in human resources’ quantity and varying degrees of competencies. There is also a lack of cross-sector cooperation because malaria control hasn’t become a priority in those sectors and they are only acting as supports to the health sector. Efforts to control malaria are considered less optimal due to the absence of malaria elimination regulations, varied human resource capabilities, and the limitation in the duties and functions of cross-sectors.